Industrial Sludge Valorization in Soil Application - Jarmila Trpčevská; Gréta Maruškinová; Martina Laubertová; Klaudia Kundráková; Dušan Oráč (Metals)
Sludges produced in the pickling line in a steel company were applied to the soil as a secondary source of nutrients. In the experiments, the addition of two types of sludge, namely neutralization sludge (NS) and phosphatization sludge (PS), was evaluated. The listed sludges are defined as non-hazardous waste and contain elements such as iron, phosphorus, zinc, and others in minor quantities. The primary motivation for using these sludges in the soil is their phosphorus content, as phosphorus is a crucial mineral nutrient. Leaf lettuce was used as a test object. The quality of the soil in which it grew can be seen from the appearance of its leaves. The period of monitoring the growth of leaf lettuce was 35 days, while the length of the leaves was measured on different days (Days 7, 14, 21, 28, and 35). Different ratios of sludge to soil were chosen (1:2, 1:1, and 2:1) for the experiments. The comparative sample for evaluation of sludge addition was leaf lettuce that grew in soil without any presence of the sludge. The application of NS to the soil in all proportions significantly accelerated the growth of the lettuce, whereas the application of PS to the soil had a negative effect on the growth. Various analytical techniques, such as SEM, EDX, XRD, HR CS FAAS, and leachability tests, were used to analyze samples of the sludges.